CHARACTERIZATION OF GENETIC STRUCTURES OF LOCAL COMMON ALFALFA (Medicago sativa L.) GENOTYPES CULTU R D IN BINGOL LOWLAND - Demirpolat, Azize; Sancar, Pelin Yilmaz; Cacan, Erdal (Parlar Scientific Publications (P S P), 2021)
Clover is the most widely grown forage crop in the world and has a higher feed value compared to all the other forage crops. It is the most popular fodder thanks to its wide adaptability, nitrogen-binding ability to the soil and the high amount of protein it eliminates from the unit area. The present study determines the genetic structures and diversity of Medicago sativa cultivated in the plains of Bingol province of Turkey. Accordingly, the genetic similarities and differences between the clover populations grown using ancestral seeds and commercially purchased seeds were investigated. The sequence analysis information of the non -coding trn regions of the chloroplast genome and the ITS region of the nuclear DNA were used for the examination of the similarities and differences. Accordingly, 31 individuals from 11 different regions were analyzed. Although the local clover genotypes grown in the plains of Bingol morphologically vary from one to another, the rate of this variation is not adequate enough for the formation of a new species. There are observed changes occurring as a result of cloves' adaptation to the environment where they grow. The products obtained by ancestral seeds and purchased certified seeds are genetically identical. This study is very important since it is the first molecular-based systematic study in which various populations of Medicago sativa species cultivated in Bingol province were included.
Keywords: Medicago sativa; Molecular structure; DNA; PCR